Qatar : Selected Issues. (IMF Staff Country Reports; Country Report, 2012)
This Selected Issues paper focuses on fiscal policy and financial linkages across banks in Qatar. The paper presents main stylized facts on the evolution of revenues and expenditures and the relationship with oil prices. It analyzes the evolution of the fiscal policy stance in the run-up to and after the global financial crisis. The paper also assesses the current fiscal stance in the context of the authorities' own objective of fully financing the budget from 2020 onward from its nonhydrocarbon revenues.